Guest Editorial Modeling and Advanced Control of Wind Turbines/Wind Farms - Hu, J.; Hou, Y.; Zhu, Z.; Xu, D.; Xu, D.; Muljadi, E.; Liu, F.; Iwanski, G.; Geng, H.; Erlich, I.; Wen, J.; Harnefors, L.; et al. (IEEE, 2017)
© 1986-2012 IEEE. The papers in this special section brings together papers focused on the recent advancements and breakthroughs in the technology of modeling and enhanced active/reactive power control of wind power conversion systems, ranging from components of wind turbines to wind farms.